2006
DOI: 10.1370/afm.529
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Vulnerability to Heart Disease in Patients with Familial Hypercholesterolemia: A Qualitative Interview Study

Abstract: PURPOSE Knowledge about the ways patients perceive their vulnerability to disease is important for communication with patients about risk and preventive health measures. This interview study aimed to explore how patients with a diagnosis of heterozygous familial hypercholesterolemia understand and perceive their vulnerability to coronary heart disease. METHODSWe did a qualitative study of 40 patients with familial hypercholesterolemia who were recruited through a lipid clinic in Norway. We elicited participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(83 citation statements)
references
References 21 publications
5
75
0
3
Order By: Relevance
“…4 A qualitative study of patients with familial hypercholesterolemia found that perceived risk may shift over time in response to social contexts and may be infl uenced by factors such as cardiac events or deaths in the family, illness experiences, or becoming a parent. 5 Another qualitative study found that patients participating in focus groups did not think that knowing their risk numbers would necessarily motivate them to change their behavior. 6 Physicians are also infl uenced by the way information is presented.…”
Section: Introductionmentioning
confidence: 99%
“…4 A qualitative study of patients with familial hypercholesterolemia found that perceived risk may shift over time in response to social contexts and may be infl uenced by factors such as cardiac events or deaths in the family, illness experiences, or becoming a parent. 5 Another qualitative study found that patients participating in focus groups did not think that knowing their risk numbers would necessarily motivate them to change their behavior. 6 Physicians are also infl uenced by the way information is presented.…”
Section: Introductionmentioning
confidence: 99%
“…It is the awakening to the presence of the at-risk relative that sparks a shift from what was once an abstract sense of risk to what Cox and McKellin (1999) refer to as an "intersubjective awareness" of risk. This process was not easy and caused a significant amount of psychosocial distress as participants tried to decipher and assign meanings to competing ideas about risk, similar to that experienced by participants in other studies Cox 2003;Cox and McKellin 1999;d'Agincourt-Canning 2005;Etchegary 2006aEtchegary , 2006bEtchegary , 2009Etchegary , 2010Frich et al 2006;Hall et al 2007;Hallowell et al 2006;Hunt et al 2000Hunt et al , 2001Marteau et al 1995;McAllister 2002McAllister , 2003Ponder et al 1996;Walter and Emery 2005;Walter et al 2004;Weiner and Durrington 2008;Weiner 2009;van Maarle et al 2003).…”
Section: Discussionmentioning
confidence: 74%
“…In particular, the notion of a "coronary candidate" (Davison et al 1991)-that is, the typical individual that develops cardiovascular disease, who is obese, who is under stress, a smoker, and inactive-illustrates how specific meanings attributed to being at risk for and managing heart disease are conveyed (Davison et al 1989(Davison et al , 1991(Davison et al , 1992Emslie et al 2001;Hunt et al 2000;Walter and Emery 2005;Weiner 2009). Several studies have highlighted how individuals juxtapose the notion of the coronary candidate against biomedical models of heart disease and their own life experience to understand their risk status, make lifestyle changes, and/or dismiss ideas about risk (Angus et al 2005;Chan et al 2011;Farrimond et al 2010;Frich et al 2006;Hunt et al 2000;Marteau et al 1995;Walter et al 2004;Walter and Emery 2005). Not surprisingly, perception of risk for heart disease is also shaped in part by the existence of visible physical or measureable factors associated with heart disease (e.g.…”
Section: Laypersons' Construction Of Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Studies of people with hypercholesterolemia have found that most people seem to view themselves as being at increased risk of CVD. [43][44][45][46] However, they may find the diagnosis hard to understand and accept if they do not feel unwell. 47,48 As a result, people may be resistant to lifestyle changes, or not take medicines to reduce cholesterol, such as statins.…”
mentioning
confidence: 99%